From reading to thinking: Student lines of thought in a seminar on Christianity and colonialism - Hovland, Ingie (Teaching theology and religion, 2019)
This article describes a seminar I taught on Christianity and colonialism. I wanted to introduce students to some content while also allowing them to practice some of the expert skills that we use in religious studies, and more specifically in my own sub-discipline, the anthropology of religion. In particular, I wanted to make more visible some of our practices of critical reading, and how these can feed into practices of complex thinking. However, given the differences between undergraduate and expert practices, what does "critical reading" and "complex thinking" look like in the undergraduate religion classroom? The article presents student readings and lines of thought through the semester, and describes how these undergraduates began to approach complex thinking on the topic of Christianity and colonialism.